Implementation of the LISCORE Model in Learning to Write Scientific Papers at the Muhammadiyah University of West Papua - Juni Syaputra; Elvi Rahmi; Zaki Mubarok; Dian Indriyani; Ainul Yaqinah; Dewi Sartika (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2026)
This study aims to analyze the effectiveness of the LISCORE model implementation in scientific writing using a Systematic Literature Review (SLR) in higher education. This study used mixed methods with students at a private university in West Papua as subjects. Data were collected through observation, questionnaires, and product documentation: student journal articles. Data analysis was conducted by combining qualitative and quantitative findings to provide a holistic view of the learning process and outcomes. The results showed that the implementation of the LISCORE model was very effective with an average score of 93.12 in the very good category. The LISCORE model can improve students' critical and systematic thinking and skills in scientific writing. These findings indicate that the LISCORE model is an innovative learning model and can be applied to improve the quality of scientific article writing learning in higher education. Therefore, the LISCORE model is recommended for adoption in research methodology and scientific writing courses, especially in the context of higher education in West Papua. Penelitian ini bertujuan untuk menganalisis efektivitas penerapan model LISCORE dalam penulisan karya ilmiah dengan Systematic Literature Review (SLR) di perguruan tinggi. Penelitian ini menggunakan metode campuran (mixed methods) dengan subjek mahasiswa di perguruan tinggi swasta di Papua Barat. Data dikumpulkan melalui observasi, kuesioner, dan dokumentasi produk: artikel jurnal mahasiswa. Analisis data dilakukan dengan menggabungkan temuan kualitatif dan kuantitatif untuk memberikan pandangan holistik tentang proses dan hasil pembelajaran. Hasil penelitian menunjukkan bahwa penerapan model LISCORE sangat efektif dengan nilai rata-rata 93,12 dalam kategori sangat baik. Model LISCORE dapat meningkatkan pemikiran kritis dan sistematis serta keterampilan mahasiswa dalam menulis karya ilmiah. Temuan ini menunjukkan bahwa model LISCORE merupakan model pembelajaran yang inovatif dan dapat diterapkan untuk meningkatkan kualitas pembelajaran penulisan artikel ilmiah di pendidikan tinggi. Oleh karena itu, model LISCORE direkomendasikan untuk diadopsi dalam mata kuliah metodologi penelitian dan penulisan ilmiah, khususnya dalam konteks pendidikan tinggi di Papua Barat.